The effect of strategic technology alliances on company performance - Hagedoorn, John; Schakenraad, Jos (Strategic Management Journal, 1994)
Abstract Strategic technology partnering between firms has become a growing subject of interest to both companies experimenting with this mode of economic organization and researchers from a wide variety of academic disciplines. In this study an effort is made to measure the effect of strategic technology partnering on companies engaged in such joint efforts. A study of the relevant literature on interfirm cooperation generates some basic understanding of this phenomenon, after which the empirical analysis is expanded with linear structural modeling of a number of relevant explanatory variables setting strategic partnering in a more complex environment.